Free radical scavenging activity and reducing power of Gnidia glauca (Fresen.) Gilg - Smitha B. Rao, M. Jayanthi, R. Yogeetha, H. Ramakrishnaiah and J. Nataraj (Journal of Applied Pharmaceutical Science, 2013)
The present study describes the free radical scavenging activity and reducing power of methanolic leaf extract of Gnidia glauca (Fresen.) Gilg.using ABTS [2, 2' azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)], FRAP (Ferric reducing antioxidant power) and nitric oxide scavenging assays. Total antioxidants were determined by phosphomolybdenum method. The results have indicated that the total phenolic content of the extract was 203.3 GAE/g and showed significant antioxidant activity with an IC50 value of 16.3µg/mL in ABTS and 360.8µg/mL in nitric oxide scavenging assays respectively. A FRAP value of 993.7 µm TE/mg of leaf extract was recorded at 30 minutes. The total antioxidant activity was 142.5 mg AAE/g of extract. The results strongly establish the significant antioxidant property of G. glauca owing to its high phenolic content.
Keywords: Gnidia glauca, antioxidant, free